Innovation, Economic Growth, Internet Use and Domestic Credit in Asia and Oceania - Deddy Marciano; Viktor Adrian (Relevance: Journal of Management and Business, 2021)
Financial Development (FD) is part of a private sector development strategy to stimulate economic growth and reduce poverty, as well as address the "costs" incurred in the financial system. As one indicator, domestic credit to the private sector refers to financial resources provided to the private sector by financial companies, such as through loans, purchases of nonquity securities, and other trade and receivables loans, which establish claims for repayment. Innovation, economic growth and internet use are three things that are closely related to FD. Therefore, the main purpose of this study is to identify the influence of innovation, economic growth and internet use on the domestic credit of three groups of countries, including developing countries and developed countries in Asia and Oceania, as well as ASEAN member groups. Panel data was used in this study and some linear regression analysis was used as an analytical model. The results showed that on domestic credit, FDI as one of the indicators of innovation only has a positive influence on the ASEAN group of member states, economic growth has a different influence on each group of countries, and the use of the internet has a positive influence on the group of developing countries and ASEAN member countries. Keywords: domestic credit, economic growth, financial development, innovation, internet use